Analysis of the Existence of Signage in Batik Lasem Tourism Village - Mandaka, Mutiawati (Journal of Architectural Research and Education, 2019)
Research on the analysis of the presence of signage in the Lasem Batik Tourism Village aims to identify signage, activities and visual areas of the Lasem written batik area, identify visual forming factors in the Lasem written batik area and get an analysis of the presence of signage in the Lasem batik tourism village area and provide recommendations on the results of the analysis so that they can provide a reference and guide for local governments/managers in carrying out the stages of developing a new tourist attraction vehicle in Rembang district.This study uses quantitative rationalistic methods, using regression analysis techniques to look for significant signage influence. Stratified random sampling is used to achieve objectivity. The population used as respondents are people with an educational background in architecture, the general public and residents who live there every day. Furthermore, the number of samples taken proportionally, while the sample area is determined using the area sampling technique. This method was taken in accordance with the purpose of the study to analyze the presence of signage in the Lasem has written batik tourism village area. Based on the findings it can be concluded that the presence of signage in commercial buildings/showrooms has a significant positive effect on the visual aesthetic of Lasem Batik Tourism Village.Â Keywords: Signage, Visual Aesthetics, Lasem Batik Tourism Village